2002
DOI: 10.1002/jgm.228
|View full text |Cite
|
Sign up to set email alerts
|

Polyethyleneimine‐based immunopolyplex for targeted gene transfer in human lymphoma celllines

Abstract: It is concluded that immunopolyplex is a good non-viral vector for specific and selective nucleic acid delivery. Immunopolyplex design allows easy replacement of the targeting element (antibody) - the streptavidin-polyplex backbone remaining intact - thereby conferring high versatility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…This antibody-mediated uptake has been successfully used to deliver plasmid DNA and antisense oligonucleotides. [13][14][15][16][17] Recently, Song et al 18 demonstrated that siRNA targeted delivered to human immunodeficiency virus-infected cells and HER2 positive cells by this strategy executed gene silencing. However, whether this promising strategy for siRNA delivery is applicable to other diseases remains unknown.…”
mentioning
confidence: 99%
“…This antibody-mediated uptake has been successfully used to deliver plasmid DNA and antisense oligonucleotides. [13][14][15][16][17] Recently, Song et al 18 demonstrated that siRNA targeted delivered to human immunodeficiency virus-infected cells and HER2 positive cells by this strategy executed gene silencing. However, whether this promising strategy for siRNA delivery is applicable to other diseases remains unknown.…”
mentioning
confidence: 99%
“…The cells were transfected by means of a chemical procedure based on PEI 25 kDa (polyethyleneimine, Sigma, Madrid, Spain) polyplexes (DNA:PEI, 1:1.41) with 5 μg/mL of plasmids, as previously described [25,32]. The transfection percentage with this method lies between 20% and 40% of total cells, as observed using the reporter EGFP gene (data not shown).…”
Section: Methodsmentioning
confidence: 91%
“…The BD OptEIA ELISA kit for mGM-CSF (Pharmingen, BD Biosciences, Madrid, Spain) was used. A time point of 5 days was chosen on the basis of prior experimental results, assessed to study cytokine production over time, using the referred transfection conditions [25,32], in order to guarantee adequate GM-CSF production according to the literature, i.e. , >35 ng/10 6 cells/24 h [28,31].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…PEI is an excellent choice for a basic building block in the design of gene carriers because of its high efficiency and abundant amino groups are amenable to conjugation 45,46,[63][64][65][66][67][68] . Further improvements in the transfection efficiency generated by PEI can often be achieved after conjugation of a cell binding ligand to PEI, thereby enabling ligand-receptor mediated endocytosis.…”
Section: Modified Pei Used In Gene Deliverymentioning
confidence: 99%